Conflict efficacy: antecedents and consequences - Steele, John Paul (Kansas State University, 2008)
Interpersonal conflict has remained a pervasive and important issue in all organizations. Despite the prevalence of workplace conflict and high individual and organizational costs, hypotheses regarding the effects of operationalizing work conflict in different ways have been largely ignored and only indirectly investigated. Study 1 experimentally examined the extent to which the process of conflict resolution was affected by context (i.e., definitional differences). Results from 507 college student participants indicated that felt conflict was manipulated by subtly changing the definition of work conflict used in survey instructions. While the manipulation was somewhat effective, the effect size was weak. Ultimately, students’ perceptions about what the conflict was about directly predicted conflict intensity, frequency, efficacy, and some resolution preferences. Results from Study 1 help refute recent criticisms that operationalizing work conflict in different ways has created a fragmented literature base, and allowed for Study 2 to move away from measurement and design issues to the more pragmatic concern of investigating the newly established and important concept of conflict efficacy, including its antecedents and consequences. Although self-efficacy is one of the most popular constructs in psychology, little research has examined conflict efficacy, or one’s assessment of their ability to resolve interpersonal conflicts. Study 2, a cross-sectional study, tested a model in which conflict efficacy (CE) was the central research variable. Study 2 attempted to establish conflict resolution skills, mastery experiences, vicarious experiences, physiological arousal, and verbal persuasion as antecedents of CE, and negative interactions at work and positive social relationships at work as key outcomes of CE. Results from 137 college students indicated that the hypothesized sources of conflict efficacy were actually better predictors of positive work relationships than either task or domain CE. Negative interactions at work and positive social relationships were predicted by task CE. In addition, frequency of negative work interactions was found to moderate the effect of conflict avoidance preference on work relationships such that avoiding was negatively related to positive work relationships when the individual experienced frequent negative interactions at work, but non-significantly related when relatively less negative interactions at work were experienced.
Keywords: Conflict; Definition; Self-efficacy; Sources; Well-being; Work Relationships; Psychology, Industrial (0624)